Theoretical approaches to the analysis of the life cycle costs of the project for the construction and reconstruction of sports and recreational facilities in Australia - Tsyfra Т.; Vilnytska, N.; Shevchuk К.І. (Ways to Improve Construction Efficiency, 2023)
The article highlights the theoretical approaches to cost analysis of the life cycle of a construction project. Most sport and recreation facilities in Australia are built or renovated with funding from the Department of Sport and Recreation. An important part of the financing process is making sure that the community can bear the real costs of operating and maintaining the facility in the future. The Life Cycle Cost Guidelines provide facility owners, architects and engineers with the tools they need to develop life cycle cost reports to be used by the department when it reviews publicly owned or community funded facilities. The Department of Sport and Recreation is committed to achieving the most desired project outcomes that reduce capital expenditure in the sport and recreation industry Developing a life cycle costing approach when considering project parameters will provide a strong and informed basis on which to make the most effective financial, economic and operational decisions decision. Life cycle costing is a key asset management tool that considers the entire life cycle of planning, acquisition, operation, maintenance and disposal of an asset. The final decision may include a number of additional factors outside of the LCCA process, such as local policies, availability of funding, rating of repair deficiencies , the ability of the industry to perform the required construction and the experience of the agency, and the accuracy of the design. The generalization of theoretical approaches shows the possibility of applying methods of financing the construction/reconstruction of objects, taking into account the analysis of the costs of the life cycle of the project of new construction and reconstruction of sports and recreational facilities not only in Australia, but also their adaptation to Ukrainian realities in the conditions of post–war reconstruction.